International relations theories : discipline and diversity - Dunne, Timothy, 1965-; Kurki, Milja, 1978-; Kušić, Katarina; Smith, Steve, 1952- (Oxford : Oxford University Press, 2024)
Unrivalled coverage of IR theories from leading experts, including historically dominant traditions such as realism, and liberalism, to theories such as postcolonialism and green theory. Featuring a new organisation to reflect the importance and focus on global IR as well as newly authored chapters on classical realism, liberalism, Marxism, and critical theories. A wide range of case studies show readers how theory can be applied to address concrete political problems. Key Features: · Expert line-up of contributors offer coverage of dominant and emerging theories and arguments from diverse perspectives · Includes coverage of historically marginalised theories, including postcolonialism and environmentalism · A case study in each chapter shows how theory can be used to explain real-world problems and dilemmas and additional questions to encourage students to analyse and evaluate the different theories for themselves · Boxes highlighting key books or articles introduce students to prominent works in the field to encourage wider reading and research interests · Spotlights on key books and articles encourage readers to go beyond the textbook and develop their research interests, exploring important works in the field.
Šesté vydání představuje nejrozsáhlejší a nejaktuálnější průvodce teoretickými přístupy k mezinárodním vztahům. Přední odborníci přinášejí komplexní přehled klasických i současných teorií – od dominantních paradigmat, jako jsou realismus a liberalismus, přes marxismus, konstruktivismus a kritické teorie, až po dlouho marginalizované přístupy včetně postkoloniálních a environmentálních teorií. Nové uspořádání knihy zdůrazňuje vzestup konceptu „globálních IR“ a reflektuje proměny disciplíny. Každá kapitola obsahuje případovou studii, která ukazuje, jak lze určité teoretické rámce aplikovat na konkrétní problémy světové politiky. Publikace tak nabízí nejen přehled teoretického myšlení, ale i praktickou oporu pro kritickou analýzu současných mezinárodněpolitických událostí.
Terminologický slovník
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: mezinárodní vztahy; dějiny mezinárodních vztahů; politické teorie; geopolitika; mezinárodní konflikty; případové studie; international relations; history of international relations; political theories; geopolitics; international conflicts; case studies